2017
DOI: 10.1161/hypertensionaha.116.08415
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Attenuation Is Associated With Newly Developed Hypertension in Men of African Ancestry

Abstract: Increased ectopic adipose tissue infiltration in skeletal muscle is associated with insulin resistance and diabetes. We evaluated if change in skeletal muscle adiposity predicts subsequent development of hypertension in men of African ancestry, a population sample understudied in previous studies. In the Tobago Health Study, a prospective longitudinal study among men of African ancestry (age range 40 to 91 years), calf intermuscular adipose tissue and skeletal muscle attenuation were measured with computed tom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…Second, compared with the SAT, the IMAT index is less affected by weight loss or weight gain in the clinical setting, making it a better imaging-derived marker for body composition in these conditions (28). Third, the IMAT index is an indicator of other underlying comorbidities (eg, diabetes and hypertension) (29,30) and may predict the allcause mortality better.…”
Section: Discussionmentioning
confidence: 99%
“…Second, compared with the SAT, the IMAT index is less affected by weight loss or weight gain in the clinical setting, making it a better imaging-derived marker for body composition in these conditions (28). Third, the IMAT index is an indicator of other underlying comorbidities (eg, diabetes and hypertension) (29,30) and may predict the allcause mortality better.…”
Section: Discussionmentioning
confidence: 99%
“…However, some recent studies have observed a positive association between LBM‐related indices and elevated BP and hypertension in young adults or postmenopausal women . These inconsistencies might be caused by differences in the calculating methods for LBM‐related indices (e.g., LBM divided by squared height instead of weight) or by additional adjustments for indices of body fat mass .…”
Section: Introductionmentioning
confidence: 99%
“…Skeletal muscle capillarization rarefaction is one of the factors that may contribute to muscle atrophy during aging [30]; skeletal muscle mass is positively correlated with capillarization. Low relative skeletal muscle mass predicts the incidence of hypertension [10,31], whereas high muscle mass protects against obesity-induced hypertension [11]. Regular exercise, as an effective approach to promote skeletal muscle hypertrophy [17,18], was shown to reduce blood pressure and improve capillary density in an obese rat with metabolic syndrome [32].…”
Section: Discussionmentioning
confidence: 99%